Diagnosis and management of penile cancer. Issue 5 (September 2016) - Kane, Clare; Sellers, Laura; Miller, Rowan
Abstract : Cancer of the penis is rare, but if caught early has a good prognosis. In this article the authors discuss the epidemiology, risk factors, presentation features and management of penile cancer.